Teaching Materials Based On Local Wisdom Ogan Komering Ilir Regency Sub-Theme Of The Uniqueness Of The Region Where I Live In Class IV Elementary School - Taslim; Siti Dewi Maharani (International Conference on Elementary Education, 2023)
Learning based on local wisdom, especially in Ogan Komering Ilir Regency, has not yet established a curriculum. It is necessary to carry out education based on local wisdom as an increase in knowledge, integrating a sense of love for the local wisdom of the area, and equipping students with manners and attitudes compared to the values and regulations that apply around or in the size of the students. Therefore, the development of teaching materials based on local wisdom was carried out. The purpose of this study was to produce a product, determine the validity, and determine the practicality of developing teaching materials based on local wisdom in Ogan Komering Ilir Regency, with the sub-theme of the uniqueness of where I live at SDN 1 Lebung Batang. Model development uses a 4D model with 3D modifications (Define, Design, Develop). The result of the research is a product of thematic teaching materials. Then, the validation results show very valid criteria. Furthermore, the results of development testing on 16 students showed very practical achievements. These results show that the teaching materials developed focusing on Ogan Komering Ilir Regency's local wisdom are feasible and can be used in elementary school learning.